PAR Digital: Uma Ferramenta Web em Prol da Educação Inclusiva - Diniz, Daniele C. S.; Pereira, Adriano C. M.; Borges, Adriana; Valladão, Adriana; Nogueira, Maria Luisa (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2024)
Special education, from an inclusive perspective, should be present at all levels of education, from early childhood education to higher education. To ensure the inclusion of students with disabilities, it is essential to adapt the curriculum and monitor the development of each individual through the Individual Development Plan. This article presents a description of the objectives and functionalities of PAR Digital, an assistive technology tool that helps teachers plan, implement, and evaluate activities for students with disabilities in regular classrooms. The platform offers a repository of differentiated strategies, based on Universal Design for Learning, to personalize teaching and monitor student progress. This tool is innovative and was developed following best architectural practices for web application design and development.